2016
DOI: 10.21037/atm.2016.11.46
|View full text |Cite
|
Sign up to set email alerts
|

Defensin-chemokine heteromeric complexes derived from heterocellular activation—a possible target to inhibit CCL5 in cardiovascular settings

Abstract: Submitted Oct 11, 2016. Accepted for publication Oct 17, 2016Oct 17, . doi: 10.21037/atm.2016 View this article at: http://dx.doi.org/10. 21037/atm.2016.11.46 Ischemic heart disease is one of the leading causes of death all over the world even after several medical technologies such as revascularization therapy including catheter intervention and surgery, and drug treatment have been developed. Among them, acute myocardial infarction (AMI) is caused by sudden occlusion of coronary arteries induced by ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…In contrast, CCL5 (RANTES), a chemokine involved in ischemia-reperfusion injury and associated with lymphocyte and monocyte recruitment [ 38 , 39 ], was lower in the CPB group in comparison to control. Patient studies in have shown CCL5 concentration decreases during CPB and return to normal values one hour after termination of CPB [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CCL5 (RANTES), a chemokine involved in ischemia-reperfusion injury and associated with lymphocyte and monocyte recruitment [ 38 , 39 ], was lower in the CPB group in comparison to control. Patient studies in have shown CCL5 concentration decreases during CPB and return to normal values one hour after termination of CPB [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%